Bioaccumulation of Aluminium Chloride in Different Organs of Freshwater Fish Labeo rohita (Ham.) - Ayyapillai, Selvam; R, Anandhan.; V, Kavitha. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The present research work was carried out to determine the bioaccumulation of aluminium chloride in the gills, liver, Kidney and muscles of Labeo rohita. Sub-lethal concentration (LC50) for 96 hours of exposure was found to be 32.5 ppm. The accumulation of heavy metal gradually increases in liver during the heavy metal exposure period. In the present study the accumulation of aluminium chloride was not found in tissues like gill, liver, kidney and muscle in control fish, whereas in treated fish the accumulation was found in the following order of liver>kidney>gill>muscle. Changes in the aluminium chloride content of muscle tissue in treated fish against the control fish were statistically significant at P<0.05. In all heavy metal, the bioaccumulation of aluminium chloride proportion was significantly increased in the tissues of Labeo rohita. This study revealed the accumulation of heavy metals in fish Labeo rohita which may act as an indicative measure to address the production, bioaccumulation and health hazardous issues of heavy metals.